Physical health and ecological momentary assessments during COVID-19: Data from the ‘Corona Health’ app usersZenodo - Johannes Allgaier; Felizitas Eichner; Stefan Störk; Peter Heuschmann; Rüdiger Pryss (Data in Brief)
The dataset published in this work is derived from the ‘Corona Health’ app, developed in collaboration with the German Robert Koch Institute (RKI) during the early stages of the COVID-19 pandemic. The smartphone application aimed to monitor the mental and physical health of the public through real-time data collection. The dataset incorporates Ecological Momentary Assessments (EMA), Patient-reported Outcome Measures (PROMs), GPS data, and digital phenotyping from app users who consented. The data includes responses from 1805 mostly German users who completed baseline and follow-up questionnaires, capturing their physical health status over time. These questionnaires cover health-related topics, including medical history, cardiovascular risk factors, lifestyle habits, and the impact of the pandemic on health behaviors. The resulting dataset offers insights into health trajectories and behaviors during the pandemic and can be utilized for further research on physical health, user engagement, and the efficacy of EMA and digital phenotyping in health monitoring. The data is publicly available under a Creative Commons license on zenodo.org/records/11093394.